2015
DOI: 10.3233/bd-140373
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to treat idiopathic granulomatous mastitis: Retrospective analysis of 40 patients

Abstract: Surgical excision still seems to be the best treatment method for IGM patients. Administration of steroids for large lesions prior to surgery may help minimize the lesion size and obtain better cosmesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
1
30
1
1
Order By: Relevance
“…According to literature, IGM typically affects parous females in the reproductive age group (1,12,13,(17)(18)(19). These findings were confirmed in our study, although there were exceptions.…”
Section: Discussionsupporting
confidence: 82%
“…According to literature, IGM typically affects parous females in the reproductive age group (1,12,13,(17)(18)(19). These findings were confirmed in our study, although there were exceptions.…”
Section: Discussionsupporting
confidence: 82%
“…In the study of Atak et al, surgical excision with administration of steroids in lesions were the best treatment method for IGM patients. In this study, 2 patients (5%) encountered with erythema nodosum, 6 patients (15%) had nipple retraction and 9 patients (22.5%) had abscess as well as the most common complaint which was breast mass (55%) (9). Complexity in treatment is more than in diagnosis because in contrast to diagnosis, there is no definitive treatment (2, 4, and 5).…”
Section: Discussionmentioning
confidence: 66%
“…It must be mentioned that FNA cannot confidently differentiate IGM and histopathological examination remains as the cornerstone (5, 6). Some studies obtained different results in terms of the treatment of these patients that suggested corticosteroids and methotrexate with surgery or treatment with corticosteroid and azithromycin, and administration of steroids in lesions in these patients (79). This study is aimed to help solve the dilemma of treatment and diagnosis of idiopathic granulomatous mastitis and answer to the question of which method can be useful for treating and diagnosing such patients, in fact we used the steroid therapy method for treating such patients and applied both MG and U/S for diagnosing such patients, and compared these methods together.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the recent literature has found corticosteroid therapy to be an effective means of GM resolution with a smaller chance of recurrence 3 5–7. There are others who still support surgical excision as primary treatment with the use of steroids to limit the size of the lesion 8. A recent study of 24 patients in New York found that medical management was most effective, with an 80% response rate to prednisone and methotrexate, and a comparable recurrence rate of 50% to previous reports 2…”
Section: Discussionmentioning
confidence: 98%